TSUNAMI HAZARD MODELING IN THE COASTAL AREA OF KULON PROGO REGENCY - Dwiana Putri Setyaningsih; Hubertus Ery Cantas Pratama Sutiono; Amelia Rizki Gita Paramanandi; Ernani Uswatun Khasanah; Tri Wahyuni; Bernadeta Aurora Edwina Kumala Jati; Muhammad Falakh Al Akbar; Wirastuti Widyatmanti; Totok Wahyu Wibowo (Ikatan Geografi Indonesia, 2022)
Kulon Progo Regency is located in the southern part of Java Island, one of Indonesia's areas that is prone to tsunami disasters. Kulon Progo Regency is prone to tsunamis because it faces a subduction zone in the Indian Ocean. Therefore, it is necessary to model tsunami inundation and map the tsunami hazard zone in the Kulon Progo coastal area. This study aims to model tsunami inundation and produce a tsunami hazard map with a tsunami height scenario of 5 meters and 10 meters. The method used in modeling tsunami inundation is using a mathematical calculation developed by Berryman-2006 using the parameters of the coefficient of surface roughness, slope, and the height of the tsunami at the coastline. The estimated tsunami inundation area is classified into a tsunami hazard index using the fuzzy logic method resulting in an index of 0 – 1, which is then divided into three hazard classes. The results of the tsunami hazard mapping with the 5 meters scenario are 15 villages in 4 sub-districts included in the hazard zone with a total area of 20672,34 Ha affected. The results of the tsunami hazard mapping with a 10 meters scenario are 26 villages in 4 sub-districts with a total area of 53042,66 Ha affected. The results of this research can be used as basic information for disaster mitigation.